Wearable Obstacle Detection for Visual Impairment People with GPS Location - Yazid, Muhammad Irfan; Othman , Maisara (Evolution in Electrical and Electronic Engineering, 2024)
In 2021, the International Agency for the Prevention of Blindness released the Vision Atlas, which showed that 43 million people worldwide are blind and 295 million people have moderate-to-severe visual impairment. For many people, mobility is a significant barrier that affects their everyday activities and social relationships. The traditional white cane is useful for navigating, but it can't identify obstacles higher than waist level. In order to overcome this constraint, this research developed a wearable, compact obstacle detection device that uses an ESP32 microcontroller and ultrasonic sensors to provide sound alerts using a buzzer. To further ensure user safety, a GPS device built within the cap delivers location updates via Telegram. The process comprised initially simulating using the Arduino IDE and Wokwi software after assembling and then testing the hardware. The design was influenced by feedback from visually impaired students at Sekolah Menengah Kebangsaan Tun Ismail in Parit Raja. The device's capacity to identify obstacle within range of 2 cm to 300 cm and provide location updates was tested for reliability, precision, and functionality. The ultrasonic sensor produced separate sound alarms for varying distances, and the results demonstrated that it could precisely identify obstacles within the designated ranges. Ensuring real-time tracking, the GPS module was dependable in sending location updates and answering requests from Telegram. For visually impaired people, the designed wearable obstacle detection cap is a useful addition to a white cane, increasing their mobility and freedom. By addressing the shortcomings of the available aids, this creative solution offers a useful and trustworthy secondary tool for obstacle detection and location.